2002
DOI: 10.1164/ajrccm.165.2.2102127
|View full text |Cite
|
Sign up to set email alerts
|

Association of Asthma Control with Health Care Utilization

Abstract: Population-based disease management should be enhanced by good risk assessment models and instruments. We prospectively evaluated the ability of a simple measure of short-term asthma control (scored 0 to 4) to predict asthma 12-mo health care utilization (HCU). A total of 5,172 adult asthma patients completed a brief questionnaire in fall 1997 to assess current level of asthma control. We then evaluated HCU for calendar year 1998. Ninety-three percent had health plan eligibility in 1998 and were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 26 publications
8
131
0
3
Order By: Relevance
“…Respondents are graded as either having or not having a control problem in each one of these 4 items; the item scores are then summed to provide a total, which ranges from 0 (no asthma control problems) to 4 (4 asthma control problems). 8,40,66,67 Skinner et al 71 developed a parent completed ATAQ version to identify children and adolescents (5-17 y old) with current problems in asthma control. This version was derived from the adult version developed by Vollmer et al 66 …”
Section: Asthma Therapy Assessment Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Respondents are graded as either having or not having a control problem in each one of these 4 items; the item scores are then summed to provide a total, which ranges from 0 (no asthma control problems) to 4 (4 asthma control problems). 8,40,66,67 Skinner et al 71 developed a parent completed ATAQ version to identify children and adolescents (5-17 y old) with current problems in asthma control. This version was derived from the adult version developed by Vollmer et al 66 …”
Section: Asthma Therapy Assessment Questionnairementioning
confidence: 99%
“…40 Vollmer et al 66 reported that only 2% of those with an ATAQ score of 0 had been hospitalized for asthma in the past year, versus 24% of those with an ATAQ score of 4. In a 12-month prospective study, 67 subjects with ATAQ scores of 3 or 4 (ie, 3 or 4 control problems) were 5 times more likely to be hospitalized, 5.4 times more likely to be seen in an emergency department, and twice as likely to have routine asthma care visits compared with subjects with no control problems.…”
Section: Validitymentioning
confidence: 99%
“…Risk assessment models have used empirical data to successfully predict, in the short term, who is most at risk for various outcomes and thus most likely to have an impact on those outcomes in the future (Eisner et al, 2002;Li et al, 1995;Magid et al, 2004;Vollmer et al, 2002). These models include many variables, such as demographic data, various indicators of current asthma control, prescription patterns, and healthcare utilization history.…”
Section: Targeting and Reaching Individuals And Communitiesmentioning
confidence: 99%
“…1,8 Given the recent increase in asthma prevalence and severity worldwide, steroid resistance has become a challenging health problem that contributes to the high costs of asthma care. 8,9 Persistent asthma has been reported to contribute to airway remodeling which can result in permanent biomechanical and pathologic alteration of asthmatic airways. 10-12 Structural changes seen in asthmatic patients can include thickening of the airway wall reticular basement membrane, formation of abnormal elastic fiber network, alterations in airway cartilage structure, angiogenesis, increase in airway smooth muscle mass.…”
Section: Introductionmentioning
confidence: 99%